Isotopic evidence on human bone for declining maize consumption during the little ice age in central western Argentina - Gil, Adolfo Fabian (2014)
This paper explores variation in maize consumption among human societies in arid environments of central-western Argentina over the last 2500 years. Increasingly positive human d13C signatures suggest a high intake of C4 resources (maize) until ca. A.D. 1400. After this time, the importance of maize in the diet drops and never reaches pre-Hispanic consumption rates, despite the known importance of maize to Inka and other late-prehistoric societies in the region. This decline appears to be related to colder temperatures during the Little Ice Age from the beginning of the 15th to the mid19th centuries.